KEBERAGAMAN ETNIS DAN POTESI KONFLIK DI KOTA KENDARI - Jabar, Aryuni Salpiana; Tunda, Amin; Sarmadan, Sarmadan; Tawulo, Megawati Asrul; Yusuf, Bakri; Azizah, lutfiana Nur; Fahrun, Ghery Safitra; Kusuma, Nada; Djayadisastra, Yoenita (Universitas Halu Oleo, 2023)
This research aims to reveal two things; (1) How various ethnicities are distributed in Kendari City and (2) How much influence ethnic diversity has on the potential for conflict in the Kendari City area. For this purpose, the type of research used is qualitative research using an exploratory approach and also assisted by quantitative data. The results of the research show that several areas can now be easily identified based on ethnicity, for example Butung Village which is inhabited by groups from the Buton tribe. The Gunung Jati area, which is also the name of the Gunung Jati sub-district in Kendari District, is inhabited by groups from the Muna tribe. The Torette family is a family group from Wawonii Island. The Totette family was identified as initially living in the Kemaraya area. The Bugis/Makassar ethnic group in Kendari City originally lived in Kasilampe, Bungkutoko Island to Mata, Bugis Village in Anduonohu and partly in the Sodoha part of Kendari Old City. Several other ethnic groups live in groups, for example the Toraja who originally inhabited the Jalan Mekar area in Kadia District as this group was in Mandonga (lorong Bulog). The Moronene ethnic group from Bombana Regency inhabits the Puuwatu area and Lorong Benteng in Kadia District. In particular, Tolaki ethnic settlements in Kendari City are spread across various areas of Kendari City. Ethnic diversity makes inter-ethnic conflict inevitable. Although various things can trigger conflict, conflict can lead to ethnic conflict, as has occurred in the city of Kendari.